Information security challenge of QR codes - Thompson, Nik; Lee, K. (Longwood University * Association of Digital Forensics, Security and Law, 2013)
The discipline of information security must adapt to new technologies and methods of interaction with those technologies. New technologies present both challenges and opportunities for the security professional, especially for areas such as digital forensics. Challenges can be in the form of new devices such as smartphones or new methods of sharing information, such as social networks. One such rapidly emerging interaction technology is the use of Quick Response (QR) codes. These offer a physical mechanism for quick access to Web sites for advertising and social interaction. This paper argues that the common implementation of QR codes potentially presents security issues that must be considered by professionals in the area. It analyzes potential privacy problems with QR codes and studies a range of devices as they may have implications for the processes and procedures used by Information Security professionals.